Geochemical Characterization of Hydrocarbon Source Rocks in the Jurassic – Cretaceous Ruvu sub-basin- within the Coastal Basin of Tanzania; Implications for Petroleum Prospecting. - Maumba, Hadija H; Kasanzu, Charles H (Tanzania Journal of Science, 2024)
In this study, we characterize hydrocarbon source rocks from the Ruvu sub-basin’s Kiwangwa well-1 using organic matter, total organic carbon (TOC), rock-eval pyrolysis and vitrinite reflectance data. Analytical results indicate fair to excellent TOC contents in the sub-basin, a feature suggesting conditions that favor organic matter production and preservation. Kerogen types II to IV are inferred for the Kiwangwa well-1 sediments. Using TOC vs S2 for the Early Jurassic and Triassic of Kiwangwa well -1 at depth intervals, good to very good source rocks are inferred. This suggests high generative organic matter suitable for hydrocarbon production. None generative organic matter window is inferred for the Cretaceous, Middle Jurassic and Late Jurassic time intervals in the sub-basin. Generation potentiality of the source rocks employing the HI and TOC parameters show that the Late Jurassic source rocks interval in the Ruvu sub-basin are gas or oil-prone. Our findings from generation potentiality in the study area indicate that the Late Jurassic source rock interval in Ruvu can offer guidance for potential prospects and gas-exploration targets. Evaluation of the degree of thermal evolution of the sedimentary organic matter using vitrinite reflectance and production index suggest marginally matured source rocks for the Late Jurassic – Middle Jurassic that indicate reworked particles.